PUBLIC EXPENDITURE AND RURAL DEVELOPMENT IN HARYANA: A REVIEW - Deswal, Deepak; Bisht, Padam S; Mukta, (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Public expenditure plays a pivotal role in shaping the socio-economic landscape of rural areas, especially in agrarian economies like Haryana. This review explores the trends, patterns, and impact of public expenditure on rural development in Haryana, focusing on critical sectors such as agriculture, rural infrastructure, education, and healthcare. By analysing data spanning recent decades, the study highlights how targeted investments in these sectors have contributed to improving rural livelihoods, enhancing productivity, and fostering inclusive growth. However, it also identifies challenges such as inefficiencies in fund allocation, gaps in policy implementation, and unequal distribution of resources. The paper emphasizes the need for strategic planning and effective governance to optimize public spending for sustainable rural development. By bridging policy gaps and fostering community participation, Haryana can achieve holistic growth and significantly enhance the quality of life in its rural areas. This review aims to provide a foundation for future research and policy reforms to strengthen the nexus between public expenditure and rural development in the state.